Investigating primary school teachers’ perceptions on the effectiveness of TikTok in enhancing speaking skills in the ESL classroom - Baharudin, Siti Nor Amira; Nair, Subadrah Madhawa; Hao, Siew Kah; Nordin, Fadzillah Binti Amer; Mechael, Patricia Devi; Mohamad, Siti Nurul Hazlina Binti; Perumal, Shubashini (Edelweiss Applied Science and Technology, 2025)
The integration of social media platforms into educational contexts has significantly transformed language acquisition methodologies, with TikTok emerging as a promising tool for enhancing English as a Second Language (ESL) instruction. This research investigates primary school educators’ perceptions regarding the effectiveness of TikTok in improving students’ speaking skills within ESL classrooms. Employing a descriptive research design, the study utilizes quantitative data collection methods. A stratified random sampling technique was applied to select a sample of 169 primary school teachers across Malaysia, ensuring representative diversity. Data collection was conducted through a structured questionnaire distributed via Google Forms, preceded by a pilot test to establish the instrument’s validity and reliability. The Cronbach’s Alpha coefficient indicated high internal consistency, affirming the instrument’s suitability for the study. Data analysis was performed using SPSS version 26, with descriptive statistics employed to interpret the findings. Results indicate that teachers perceive TikTok as an engaging and effective platform for fostering key language skills such as fluency, pronunciation, and confidence in speaking English. The platform’s interactive features are also recognized for promoting creativity and facilitating collaborative learning among students. Despite these positive perceptions, concerns persist regarding content appropriateness, accessibility issues, and challenges related to classroom integration. The study underscores the importance of developing structured frameworks for incorporating TikTok into ESL curricula to optimize its benefits while addressing potential obstacles. These findings contribute to the ongoing discourse on technology-enhanced language learning and its implications for contemporary educational practices. Pedagogically, the study suggests that TikTok can serve as a viable supplementary tool for teaching ESL speaking skills, provided that appropriate guidelines and strategies are implemented to ensure effective and responsible use.